Nanocellulose production from African oil palm rachis and sugarcane bagasse - Jirón-García, Eddy (2022)
African oil palm rachis and sugarcane bagasse were used as raw materials to produce cellulose nanofibrils by hybrid method which combine chemical treatment and mechanical rupture. The cellulose obtained from both raw materials after hydrolysis was characterized by Infrared Spectroscopy, Thermogravimetric Degradation Analysis, Scanning Electron Microscopy, Fluorescence Microscopy and X-ray Diffraction. At the end of the mechanical rupture, Transmission Electron Microscopy was performed at the nanofibrils to determine their size. A lignin removal percentage of 74,1 % was observed for the african oil palm rachis and 65,6 % for the sugarcane bagasse after chemical treatment; which generated microcellulose of 6-12 µm and 10-18 µm for the rachis and bagasse respectively. The mechanical rupture treatment with the high-power sonifier produced nanofibrils of 19-24 nm for the palm rachis and 9,22-12 nm for the cane bagasse; with a Crystallinity Index of 70% in both cases.